Vandetanib in a Child Affected by Neurofibromatosis Type 1 and Medullary Thyroid Carcinoma with Both NF1 and Homozygous RET Proto-oncogen Germ-line Mutations - Begümhan Demir Gündoğan; Fatih Sağcan; Sevcan Tuğ Bozdoğan; Yüksel Balcı; Ferah Tuncel Daloğlu; Elvan Cağlar Çıtak (Galenos Yayincilik, 2021)
Cases of neurofibromatosis type 1 (NF1)-associated medullary thyroid carcinoma (MTC) or C-cell hyperplasia are rarely associated with other endocrine tumors or cases with a multiple endocrine neoplasia type 2. In these patients, mutations were detected in the NF1 gene but no mutations were detected in the RET gene. Although vandetanib has been shown to improve progression-free survival in adults with advanced MTC, data in pediatric patients are limited. Herein, we report the use and outcome of vandetanib in a pediatric MTC case in which NF1 gene and RET proto-oncogen mutation were identified together.